(untitled) (Ágora de Heterodoxias, 2026)
This article analyzes two digital works by the Spanish visual artist Guillermo Arismendi. To this end, it draws on Edgar Morin’s complexity theory and Peter Sloterdijk’s theses on the art of the future. Methodologically, it employs a single-case approach combined with theoretical sampling. Furthermore, the study hypothesizes that Arismendi’s digital abstractionism constitutes part of a possible art of the future, where the configuration of a new mental state leads to perceiving art as a therapeutic and compensatory space. The results confirm this conjecture, particularly through the observed correlation between the attributes of Arismendi’s painting - compositional complexity and digital chromatism with a predominance of blues- and an art of the future understood as an art of impatience and immediate gratification. Precisely, this concatenation fosters within Arismendi’s work the deployment of aesthetic-therapeutic forces as a sign of a mental presence capable of facing the complexity and posthistorical barbarity.